Hannah Arendt and the specter of totalitarianism - LaFay, Marilyn (Critical political theory and radical practice, 2014)
"This book treats Hannah Arendt as a distinctly political writer who attempts to carve out a way in which humanity, poised between the Holocaust and the atom bomb, might reclaim its position as the creators of a world fit for human habitation. Marilyn LaFay argues that Arendt tries to bring a humanity into modernity, rejecting the argument that Arendt is an 'antimodernist lover of the Greek polis.' Rather, Arendt tries to politically reconcile the potential of humanity with the demands of the modern condition: she encourages us to locate and use the expressive element of the modern for our political ends. This work identifies the paradox of Arendt's choice of an expressive, existentialist interpretation of politics over that of a politics of vision and imagination, concluding that Arendt's politics leads to little more than political aesthetics"--